Enhancing The Data Security by using Audio Steganography with Taylor Series Cryptosystem - Gençoğlu, Muharrem Tuncay; Gençoğlu, Muharrem Tuncay (My University, 2021)
Especially in recent years, the security of information and computer systems appears to be a very important issue. Because the heavily used communication network has made life easier as well as accompany serious security problems. To solve these problems, cryptography and steganography have been widely used. To present a more secure model for audios, a simple and secure stego-crypto method is presented. In this work, the hidden data is encrypted by the proposed Taylor series based encryption method and the encrypted data are hidden audio signals by applying the least significant bit (LSB) method. A real-world application is implemented in the proposed model. According to the results, the used encryption model is more efficient than AES. The results and findings demonstrated that this model can be used in a communication security system.
Keywords: Cryptography; Audio Steganography; Data Steganography; Text Steganography